Alternative Internet Radio, Press Freedom and Contentious Politics in Hong Kong, 2004–2014 - Leung, Dennis K. K. (Javnost-The Public, 2015)
This article analyses the rise and development of alternative Internet radio in Hong Kong in the past decade in tandem with the changing status of press freedom and contentious politics in the city. The article illustrates that alternative Internet radio first emerged a decade ago as the self-defence of the civil society against political encroachments on the media. Cognisant of the political potential of alternative Internet radio, pro-democracy radical political parties and social activists have subsequently appropriated this new medium to facilitate and engage in contentious politics. In the face of tightening political control of mainstream media in recent years, alternative Internet radio has become a “safe haven” for the exited rebel voices. Despite the considerable political significance of alternative Internet radio (and alternative Internet media in general) at this moment, its prospect remains uncertain due to potential regulatory control and increasing political pressures on Internet media in the future.